Does bladder outflow obstruction obfuscate the traditional clinical factors that are used to assess the risk of prostate cancer at rapid‐access diagnostic clinics? - Thomas Philip Cahill; Samuel Joseph Withey; Steve Hazell; Declan Cahill; Netty Kinsella (BJUI Compass)
Abstract Objectives To understand whether bladder outflow obstruction influences the association between traditional clinical predictive factors, particularly prostate‐specific antigen (PSA) density and clinically significant prostate cancer (csPCa). This will help facilitate effective and evidence‐based triaging of patients in rapid‐access clinics. Materials and Methods We retrospectively analysed prospectively collected data from 307 suspected prostate cancer patients who underwent diagnostic biopsy from 2019 to 2023 at a single, high‐volume, specialist cancer centre. Uroflowmetry testing generated two cohorts: patients with bladder outflow obstruction and non‐obstructed patients. The cohort characteristics between the groups were compared and logistic regression analyses were performed to assess associations between clinical predictive factors (age, PSA density, ethnicity, family history, digital rectal examination, urinary symptom severity and magnetic resonance imaging using the PI‐RADS scoring system) and clinically significant prostate cancer (csPCa) on biopsy (defined as International Society of Urological Pathology grade of greater than or equal to two). Results The obstructed group (n = 80) had significantly larger prostates and worse symptom severity (p < 0.05). There was no significant difference between the other predictive factors or csPCa compared to the non‐obstructed (n = 227) cohort. Multivariable logistic regression analysis showed age, PSA density, an abnormal digital rectal examination and scoring PI‐RADS 4–5 on magnetic resonance imaging were all significantly associated with csPCa in the non‐obstructed cohort (p < 0.05). Contrastingly, only symptom severity and scoring PI‐RADS 5 were significantly associated with csPCa for the obstructed patients (p < 0.05). Conclusion In the presence of bladder outflow obstruction, traditional predictive variables such as age, PSA density, digital rectal examination and scoring PI‐RADS 4 are not associated with csPCa. This study suggests that using these predictive variables to triage patients in rapid‐access clinics with a patient who has bladder outflow obstruction could lead to the overuse of invasive biopsy.